2010
DOI: 10.4269/ajtmh.2010.09-0440
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assurance of Rapid Diagnostic Tests for Malaria in Routine Patient Care in Rural Tanzania

Abstract: † In the WHO evaluation, parasite detection rate was defined as the percentage of malaria samples in a test panel giving a positive result by two RDTs per lot at the lower parasite density (200 parasites/µL), and a single RDT per lot at the higher parasite density (2,000 or 5,000 parasites/µL). Thus, it is a combined measure of positivity rate, along with inter-test and inter-lot consistency. Abstract. Histidine-rich protein II (HRP2)-based malaria rapid diagnostic tests (RDTs) have shown high sensitivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 10 publications
2
41
1
1
Order By: Relevance
“…28,29 In addition, adequate healthcare worker training and supervision is strongly recommended to achieve and maintain high performance of these tests. 27,30,31 In our study, we found the sensitivity of ICT Malaria P.f. to be comparable to highquality microscopy.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…28,29 In addition, adequate healthcare worker training and supervision is strongly recommended to achieve and maintain high performance of these tests. 27,30,31 In our study, we found the sensitivity of ICT Malaria P.f. to be comparable to highquality microscopy.…”
Section: Discussionmentioning
confidence: 72%
“…It is important to remember that our study staff was trained in the use of RDTs and good performance of these tests is highly associated with appropriate training and supervision of healthcare workers and laboratory staff. 30,32 This study has several limitations. First, it was an HF-based survey and, by limiting the information on malaria prevalence to only patients seen at HFs, we may have poorly estimated the true burden of malaria in Maputo City.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 For this analysis, we used the results of the RDT, which are characterized by high sensitivity but lower specificity as the tests detect HRP2 antigen that persists in the bloodstream after clearance of the parasite. 31 Children with a positive RDT were offered treatment with weight-based dosing of Coartem ® artemether/ lumefantrine (Novartis Pharma AG, Basel, Switzerland) at the household according to guidelines from the Uganda NMCP. 32 We analyzed data on Hb levels among children under 60 months and assessed sociodemographic and clinical risk factors associated with anemia using weighted univariate and bivariate analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Minimal training is needed to use RDTs, 22,23 and assuming good manufacturing quality accompanied by effective quality assurance systems, several *Address correspondence to Michael Aidoo, Centers for Disease Control and Prevention, 1600 Clifton Road, Mail Stop-A06, Atlanta, GA 30333. E-mail: maidoo@cdc.gov tests will perform well in the field.…”
Section: Support For Rapid Diagnostic Test Rollout and Usementioning
confidence: 99%